Activated α2-macroglobulin induces cell proliferation and mitogen-activated protein kinase activation by LRP-1 in the J774 macrophage-derived cell line - Bonacci, Gustavo Roberto (2007)
The low-density lipoprotein receptor-related protein-1 (LRP-1) is an endocytic receptor of activated forms of the proteinase inhibitor alpha(2)-macroglobulin (alpha(2)M*). It has been proposed that alpha(2)M* and LRP-1 modulate diverse cellular processes, including cell adhesion, proliferation, and migration, which are involved in inflammation and tumor progression. However, relatively little is known about the role of alpha(2)M*/LRP-1 interaction on these processes. In this work, we demonstrate that alpha(2)M* binding to LRP-1 induces cell proliferation and MAPK activation in the J774 macrophage-derived cell line, which were blocked by RAP, an antagonist of LRP-1-binding ligands, and by PD980059, a specific inhibitor for the Mek1-ERK1/2 pathway. In addition, we demonstrate that LPS, a bacterial product that it is known to down-regulate the LRP-1 expression on macrophage, abrogated the signaling activity triggered by alpha(2)M* on LPS-treated J774 cells. These results suggest that alpha(2)M*/LRP-1 interaction constitutes a key role in the macrophage functioning during inflammation and cancer.